Autoimmune and Rheumatic Manifestations Associated With COVID-19 in Adults: An Updated Systematic Review - Tang, Kuo-Tung; Hsu, Bo-Chueh; Chen, Der-Yuan (Frontiers in Immunology, 2021)
Background: Numerous cases of the coronavirus disease 2019 (COVID-19) with autoimmune and rheumatic manifestations have been reported. Despite the available reviews that summarized its autoimmune/rheumatic manifestations, a systematic approach is still lacking. Therefore, we conducted a comprehensive systematic review in order to give an overview upon these rare but clinically significant manifestations. Methods: We performed a literature search of PubMed and EMBASE as of October 9, 2020. All articles relevant to either systemic or organ-specific autoimmune and rheumatic manifestations potentially associated with COVID-19 were collected. The reviewed literature were limited to adults ≥18 years. Results: Although most of the existing evidence was based on case reports or case series without a long-term follow-up, a variety of autoimmune/rheumatic manifestations were associated with COVID-19. The manifestations that have a consistent association with COVID-19 include autoimmune cytopenia, cutaneous vasculitis, encephalitis, and Guillain-Barre syndrome. Such association is conflicting as regards to antiphospholipid syndrome, hemophagocytic lymphohistiocytosis, and myasthenia gravis. Conclusion: Our systematic review indicated the potential of the COVID-19 virus to trigger a myriad of autoimmune and rheumatic manifestations, which should be considered amid global efforts to combat COVID-19.